STRUKTUR UKURAN, HUBUNGAN PANJANG BERAT DAN IKAN LAYAK TANGKAP PADA RUMPON PORTABLE DI PERAIRAN ACEH BARAT MEULABOH - Muhammad Rizal; Jaliadi Jaliadi (Journal of Aceh Aquatic Sciences, 2017)
Fishing has contributed to an increase in the fishing economy is reasonably sufficient especially in the region of Meulaboh. The intensity of the high current arrests tend to ignore resource sustainability of fish. The increasing activity of catching fish can experience a decrease in fish stocks at rumpon, however this will negatively impact populations and patterns of growth in terms of length and weight of the fish. This research aims to analyze the frequency of long length-weight relationships, and the fish that was caught on the rumpon portable in West Aceh waters. The data collected in the form of the data length (fork length) were measured using a meter roll with a maximum length of 5 metres. Fish obtained from catches in experimental fishing for 30 trip using a capture tool output rod and assistive tools rumpon portable. The collected data is analyzed the frequency of long, long relationship of weight and length of fish caught prediction. The catch as much as 472 tail, the dominant fish caught during research on the measure of 17.5 cm. length of the tuna was first caught on the size 24.9 cm 15.5 cm kites, fish, yellow tail fish 14.7 cm and yellow 14.6 cm trevally fish. Length weight relationship mackerel krei y= 0, 0089x3,1293 R² = 0.9995, flying fish, y= 0 0068x3,1414 R² = 0.9987 yellow tail fish, y = 0, 0178x2,8971 R² = 0.9935 and trevally fish yellow y = 0, 0256x2,7779 R² = 0.9854.